Conventional intensive versus LED intensive phototherapy oxidative stress burden in neonatal hyperbilirubinaemia of haemolytic origin. (2nd January 2020) - Mokhtar, Wesam A.; Sherief, Laila M.; Elsayed, Hany; Shehab, Mohamed M.; El Gebaly, Sherief M.; Khalil, Atef M. M.; Sobhy, Mohamed; Kamal, Naglaa M.
ABSTRACT: Background : Phototherapy causes oxidative stress which is of particular importance in neonates because of the increased susceptibility of neonatal red blood cell membranes to oxidative damage. Aim : To evaluate the oxidant/antioxidant status in neonates with haemolytic hyperbilirubinaemia before and after exposure to two different intensive phototherapy light sources. Patients and Methods : A randomised controlled study was undertaken in 54 full-term neonates with indirect haemolytic hyperbilirubinaemia admitted to a neonatal intensive care unit in the first week of life. They were randomly divided into two equal groups. Group 1 infants were exposed to intensive conventional phototherapy (Bilisphere 360) and Group 2 were exposed to an intensive light-emitting diode (LED) phototherapy device (Bilitron bed 3600). Total serum bilirubin (TSB), total oxidative stress (TOS), total antioxidant capacity (TAC) and the oxidative stress index (OSI) were measured before and 48 hours after initiation of phototherapy. Results : There was a significant decrease in TSB after phototherapy in both groups ( p < 0.001). The TOS and OSI were significantly increased after phototherapy in both groups ( p < 0.001) but more so in Group 1 with conventional phototherapy ( p = 0.05 and 0.01, respectively). TAC was significantly decreased after phototherapy in both groups ( p < 0.00) but more so in Group 1 ( p = 0.03). There were significant increases in the incidence of dehydration, hyperthermia and skin rash in the conventional compared with the LED phototherapy group ( p = 0.02, 0.01 and 0.02, respectively). However, there was a significant increase in the incidence of hypothermia in the LED compared with the conventional phototherapy group ( p = 0.001). Conclusion : Both intensive conventional and LED phototherapy are equally effective in decreasing TSB, but intensive LED phototherapy is safer than intensive conventional phototherapy with regard to oxidative stress and oxidant/antioxidant imbalance. Abbreviations: DSB: direct serum bilirubin; G6PD: glucose-6-phosphate dehydrogenase enzyme; LED: light-emitting diode; OSI: oxidative stress index; TAC: total antioxidant capacity; TOS: total oxidative stresses; TSB: total serum bilirubin